Intersectionality reading of Caribbean-American in-transit female narratives : Kincaid's Lucy and Nunez' Boundaries - PourAli, Soheyla; Eslamieh, Razieh; Chavoshian, Shohreh (Penerbit Universiti Kebangsaan Malaysia, 2022)
While large bulk of recent scholarship has reflected growing attention to migration, there has been little focus on the evolving intersected marginalization and social inequalities of in-transit women in the host land. The present study addresses the evolving phenomena of intersectionality in the context of larger structures of racism, sexism, classism and the legacies of colonialism. Intersectionality refers to the interlocking oppression experience produced by the interaction of social, economic, political, cultural and racial factors. Intersectionality both as a concept and theory is to uncover the underlying interrelated and interconnected layers of dimensions including but not limited to race, class, gender, sex, ethnicity, age, nation and dis/ability which generate a distinct mode of oppression, subordination and inequality for an individual. In this study, the intersectionality related coined concept diaspora-intersectionality is presented to acknowledge the role of the overlapping interplay of interconnected factors in social exclusion, marginalization, class discrimination, genderization, and social locationality of diasporic female characters in the two Caribbean women writers' works: Jamaica Kincaid's Lucy (1987) and Elizabeth Nunez's Boundaries (2011).The authors have a number of themes in common, both Caribbean descent with hyphenated identity living alternately in the USA and the Caribbean. Their protagonists are also very similar; both immigrated to the West to earn professional experience and seek happiness. Both works abundantly overlap in portraying intransit Caribbean females whose positionings in the host land are hardly affected by intersectional patterns resulting to translocational marginality, class-conscious exclusion and social inequality. Thereby, intersectionality theory is beneficially opted to explore how diaspora context shapes marginalized shifting identities and how dominant power systems construct and neutralize social injustice and inequality for diasporic intersected individuals in the narratives.